Referrals to secondary care in an outpatient primary care walk-in clinic for refugees in Germany: results from a secondary data analysis based on electronic medical records. Issue 10 (22nd October 2020) - Schäfer, Ingmar; Oltrogge, Jan Hendrik; Pruskil, Susanne; Mews, Claudia; Schlichting, Dana; Jahnke, Martin; Wagner, Hans-Otto; Lühmann, Dagmar; Scherer, Martin
Abstract : Objectives: The aims of our study were to describe the disease spectrum of refugees, to analyse to what extent their healthcare needs could be met in an outpatient primary care walk-in clinic and which cases required additional services from secondary care (ie, outpatient specialists or hospitals). Design: Retrospective longitudinal observational study. Setting: The study was based on routine data from a walk-in clinic in the largest central first reception centre in Hamburg, Germany between 4 November 2015 and 21 July 2016. Participants: 1467 asylum seekers with 4006 episodes of care (ie, distinctive health problems) resulting in 5545 consultations. The patients were 60% men and had a mean age of 23.2 years. About 90% of the patients were from Central Asia or from the Middle East and North Africa. Primary and secondary outcome measures: The endpoint of our analyses was referral to secondary care. Time to event was defined as days under treatment until the first referral. Predictor variables were the patients' diagnoses grouped in 46 categories. The data set was analysed by Cox regression allowing for multiple failure times per patient. This analysis was adjusted for age, sex and country of origin. Results: Referrals to secondary care occurred in 15.5% of the episodes. The diagnosis groups with the highest referral rates were 'eye' (HR 4.9; 95% CI 3.12 to 7.8; p≤0.001), 'teeth/gum symptom/complaint or disease' (3.51; 2.52 to 4.9; p≤0.001) and 'urological system/female or male genital' (2.50; 1.66 to 3.77; p≤0.001). Age, sex and country of origin had no significant effect on time until referral. Conclusions: In most cases, the walk-in clinic physicians could provide first-line medical care for the health problems of patients not integrated in the German healthcare system. Additional resources were needed particularly not only for visual impairment and dental problems but also for psychological disorders, antenatal care and certain infections and injuries.